Factors for Treatment Failure After Fecal Microbiota Transplantation in Clostridioides difficile Infection - Soo-Hyun Park; Jung-Hwan Lee; Suhjoon Lee; Jongbeom Shin; Boram Cha; Ji-Taek Hong; Kye Sook Kwon (Microorganisms)
Recently, fecal microbiota transplantation (FMT) has been introduced as an effective treatment option for Clostridioides difficile infection (CDI). However, the risk factors associated with FMT treatment failure have not been well demonstrated. Therefore, we aimed to investigate the risk factors of treatment failure or recurrence after FMT for CDI. This retrospective study included 124 patients with CDI who underwent FMT at Inha University Hospital between November 2017 and August 2021 and were followed up for 8 weeks after FMT for symptoms of CDI. FMT failure was defined as diarrhea recurrence or a positive stool test. We assessed the risk factors for treatment failure, including comorbidities, antibiotic use pre- and post-FMT, and the number of CDI episodes before FMT. Ninety-three patients (75%) experienced symptom improvement <7 days after FMT, while treatment failure occurred in 40 patients (32.3%). Multivariate analysis revealed that males had a lower symptom improvement rate <7 days after FMT (p = 0.049). Patients using antibiotics after FMT showed a higher rate of recurrence or treatment failure in <8 weeks (p = 0.032). Patients requiring antibiotics after FMT should be considered at higher risk of treatment failure. Careful antibiotic stewardship, particularly minimizing non-essential antibiotic use before and after FMT, may significantly enhance treatment outcomes. Further large-scale prospective studies are warranted to confirm these findings and develop targeted antibiotic management protocols for improving the efficacy of FMT in CDI treatment.